2013
DOI: 10.1902/jop.2012.120255
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Periodontitis and Tooth Loss Associated with Glycemic Control in Individuals Undergoing Periodontal Maintenance Therapy: A 5‐Year Follow‐Up Study

Abstract: PGC individuals, especially smokers, presented with a higher progression of periodontitis and tooth loss compared to NDC and GGC individuals. This result highlights the influence of glycemic control in maintaining a good periodontal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 47 publications
4
82
1
Order By: Relevance
“…Costa et al 8) showed that smoking and diabetes were risk factors for tooth loss in patients undergoing supported periodontal therapy after periodontal treatment. Neither smoking nor diabetes were associated with tooth loss in the present study, however, although the reason for this disparity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al 8) showed that smoking and diabetes were risk factors for tooth loss in patients undergoing supported periodontal therapy after periodontal treatment. Neither smoking nor diabetes were associated with tooth loss in the present study, however, although the reason for this disparity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The interrelation between more severe PD and DM is established 8,32 and there are evidences on the importance of cytokine analysis in T2DM evolution 29 and therapy blockade 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of type 2 diabetes worldwide, which is increasing rapidly, represents a significant burden to human health because of its numerous and often systemic complications. This challenge also affects Brazilian´s population [2][3][4] . The World Health Organization estimates that there are 220 million adults with diabetes in the world today and that in 2030 this number may double.…”
Section: Introductionmentioning
confidence: 99%